A simplified approach for computer-aided education of network reconfiguration in radial distribution systems - Prasad, K.; Sahoo, N. C. (JOHN WILEY & SONS INC, 2007)
In the present electrical engineering curriculum, power distribution engineering is one of the core courses offered to the students with power systems specialization. Since the distribution systems are mostly radial, the topics related to radial distribution system (RDS) are emphasized in this course. In RDS, network reconfiguration is frequently performed for optimizing system performance. Before the reconfiguration operation is physically performed, it is necessary to have computer-aided performance assessment of the reconfigured RDS from load flow analysis. For students' education, it is necessary that the students should familiarize themselves with computer simulation of RDS reconfiguration followed by load flow analysis. T he purpose of this paper is to clearly and illustratively explain the various underlying sub-processes involved in the simulation experiment of RDS reconfiguration. The pseudo-codes in the form of flowcharts and complete C-language program codes for RDS reconfiguration are also included. (C) 2007 Wiley Periodicals, Inc.